On the asymptotic behavior of a boltzmann-type price formation model - Burger, Martin; Caffarelli, Luis; Markowich, Peter A.; Wolfram, Marie-Therese; et al. (Communications in Mathematical Sciences, 2014)
In this paper we study the asymptotic behavior of a Boltzmann-type price formation model, which describes the trading dynamics in a financial market. In many of these markets trading happens at high frequencies and low transaction costs. This observation motivates the study of the limit as the number of transactions k tends to infinity, the transaction cost a to zero and ka=const. Furthermore we illustrate the price dynamics with numerical simulations © 2014 International Press.
WWU::100106